Digital Marketing Communication Model on Digibank Indonesia - Susilo, Daniel (International Journal of Science, Technology & Management, 2023)
Digibank, a progressive private bank, has consistently targeted younger demographics with its campaigns. Offering free administrative charges on transfers, Digibank has positioned itself as a brave and innovative player in the financial sector. However, its promotion of student loans raises questions about the alignment between its financial literacy efforts and its product offerings. This paper explores this paradox within Digibank Indonesia's Instagram campaigns. The study employs content analysis to investigate posts from Digibank Indonesia's Instagram account over a one-year period (2023-2024). The focus is on messages related to financial literacy, free transfer services, and student loans. The findings reveal that while Digibank promotes financial literacy and offers attractive banking services such as free transfers, it also actively promotes student loans. This marks a significant acknowledgment that student loan debt is an emerging issue in Indonesia. These findings have implications for both policy-makers and consumers. For policy-makers, understanding how banks communicate about products like student loans can inform regulations around financial advertising. For consumers, particularly young people who are the primary targets of these campaigns, this research highlights the need for critical engagement with banking advertisements.